Systematic review and consensus definitions for the Standardized Endpoints in Perioperative Medicine (StEP) initiative: cardiovascular outcomes. (January 2021) - Beattie, W. Scott; Lalu, Manoj; Bocock, Matthew; Feng, Simon; Wijeysundera, Duminda N.; Nagele, Peter; Fleisher, Lee A.; Kurz, Andrea; Biccard, Bruce; Leslie, Kate; Howell, Simon; Landoni, Giovanni; et al.
Abstract: Background: Adverse cardiovascular events are a leading cause of perioperative morbidity and mortality. The definitions of perioperative cardiovascular adverse events are heterogeneous. As part of the international Standardized Endpoints in Perioperative Medicine initiative, this study aimed to find consensus amongst clinical trialists on a set of standardised and valid cardiovascular outcomes for use in future perioperative clinical trials. Methods: We identified currently used perioperative cardiovascular outcomes by a systematic review of the anaesthesia and perioperative medicine literature (PubMed/Ovid, Embase, and Cochrane Library). We performed a three-stage Delphi consensus-gaining process that involved 55 clinician researchers worldwide. Cardiovascular outcomes were first shortlisted and the most suitable definitions determined. These cardiovascular outcomes were then assessed for validity, reliability, feasibility, and clarity. Results: We identified 18 cardiovascular outcomes. Participation in the three Delphi rounds was 100% ( n =19), 71% ( n =55), and 89% ( n =17), respectively. A final list of nine cardiovascular outcomes was elicited from the consensus: myocardial infarction, myocardial injury, cardiovascular death, non-fatal cardiac arrest, coronary revascularisation, major adverse cardiac events, pulmonary embolism, deep vein thrombosis, and atrial fibrillation. These nine cardiovascular outcomes were rated by the majority of experts as valid, reliable, feasible, and clearly defined. Conclusions: These nine consensus cardiovascular outcomes can be confidently used as endpoints in clinical trials designed to evaluate perioperative interventions with the goal of improving perioperative outcomes.